(untitled) (Public Sector Economics - submission site, 2022)
Lack of information on the adequacy of fiscal measures undertaken in the COVID-19 crisis and its long-term adverse effects on economic growth and labor market outcomes has raised debates about the impact of fiscal austerity and fears of slower recovery from the ongoing economic downturn. This paper analyzes the short and long-term effects of the fiscal policy measures undertaken in the COVID-19 crisis in the EU-27. For the short-term estimation, we use Okun’s law. To examine the long-run effects, we use the concept of potential output using a production function approach. The findings from this paper are that in the short-term, fiscal measures were generally effective. In the long-term, the COVID-19 crisis would have had a negative and permanent effect on the potential GDP growth if the policymakers had undertaken no fiscal measures.